Produção e percepção da vogal alta anterior átona final no português brasileiro - Matheus Freitas Gomes (2023)
This dissertation investigates how phonetic-based effects characterise the implementation in production and perception of the variable unstressed word-final high front [ɪ] vowel in Brazilian Portuguese considering different sets of words. Two experiments were designed to test the hypotheses in which 20 speakers from Belo Horizonte – Minas Gerais took part. A production experiment was carried out as a figure naming task. Native words and loanwords which present or do not present a final orthographic <E> letter were analysed (ex.: leque ‘fan’ [ˈlɛkɪ] ~ [ˈlɛk]; make ‘make-up’ [ˈmeɪkɪ] ~ [ˈmeɪk]; drink ‘drink’ [ˈdɾi͂kɪ] ~ [ˈdɾi͂k]). A perception experiment was carried out as a vowel counting task in nonce words. Results show that: (1) differences in the phonetic detail, captured by segmental duration in the word, characterise the emergence of novel phonic patterns; (2) different orthographic patterns influence the implementation of the phenomenon in the lexicon; (3) differences in the phonetic detail shown in production data may influence the perception of illusory vowels, which is the perception of vowels with no articulatory-acoustic correlate. Exemplar Theory and Complex Dynamic Systems Theory support the discussion. With these findings, we argue that the phenomenon should be interpreted as complex, emergent and gradual, that orthographic information may contribute to the investigation of phonological phenomena and that the phonetic detail should be included in the analysis of the mapping mechanisms related to phonic perception.